Analysis and design of a new fault‐tolerant digital comparator based on nano‐scale quantum technology. (31st July 2022) - Jiao, Yuhan
Summary: Quantum‐dot cellular automata (QCA) is a transistor‐free technique for designing digital circuits. It is a substitute for CMOS technology for producing low‐energy and high‐speed digital circuits. In addition, the digital comparator is an important digital circuit; its fault‐tolerant design is examined in this article. Additionally, a coplanar QCA‐based fault‐tolerant comparator circuit with a small number of cells is suggested. The QCADesigner is used to achieve exact simulation results. The suggested fault‐tolerant comparator requires 63 QCA cells, uses 0.8 μ m 2, and has three clock cycles delay in accomplishing its purpose. Furthermore, simulation results demonstrate that the suggested comparator design with a limited number of cells can achieve a fault‐tolerant of 80% against cell missing, extra cell, cell displacement, and cell rotation faults.